Bridge modification 2 stronger and safer bridges : proceedings of the International Conference organized by the Institution of Civil Engineers and held in London on 7 November 1996 - Pritchard, Brian (Thomas Telford, 1997)
Following from the successful Bridge Modification conference in 1994, this volume contains papers describing the issues thinking, and technology behind the assessment and improvement of bridges. The papers are grouped under the headings: policy improved assessment; and case studies. This volume is useful to bridge engineers.
Keywords: Bridges -- Design and construction -- Congresses.; Bridges -- Specifications -- Congresses.; Bridges -- Maintenance and repair -- Congresses.; elektronické knihy; electronic books